Euthymic despite pain: the role of cognitive reappraisal and experiential avoidance in autoimmune inflammatory rheumatic diseases—a cross-sectional study - De Vincenzo, Francesco; Iani, Luca; Alessio, Chiara; Navarini, Luca; Currado, Damiano; Marino, Annalisa; Contardi, Anna (Frontiers in Psychology, 2024)
Pain is a central feature of inflammatory rheumatic diseases and is associated with psychological distress. Pain is widely recognized not as a mere physical sensation, but as a complex, multidimensional phenomenon with an affective component. A plethora of research has conceptualized adaptation to pain by focusing on minimizing the pain experience. However, pain in autoimmune inflammatory rheumatic diseases is often neither avoidable nor curable. This crosssectional study aimed to investigate the processes explaining how pain intensity may be associated with low well-being and why some patients may live well despite pain. Drawing upon the psychological (in)flexibility model and the process model of emotion regulation, we propose that cognitive reappraisal moderates the association between pain and euthymia through experiential avoidance. Ninety-seven patients with rheumatoid arthritis, psoriatic arthritis, or axial spondyloarthritis were included for analyses (mean age = 53.4; mean time since diagnosis = 9.2 years). Most patients were women (75%), married/cohabitant (71%), and attended high school (47%). Results indicate that experiential avoidance may explain how severe pain is associated with lowered euthymia. This indirect negative effect of pain intensity on euthymia became non-significant at high levels of cognitive reappraisal, suggesting that cognitive reappraisal may serve as a protective factor for patients with autoimmune inflammatory rheumatic diseases. This study paves the way for future research in this promising context by providing an initial step towards integrating emotion regulation and psychological inflexibility in pain conditions.